Unraveling Takayasu arteritis and antiphospholipid syndrome in the context of ischemic stroke - Goyal, Anmol; Dav, Rajvi; Naithani, Nardeep; Rawat, Arti; Singh Nanda, Vaishnav (Indian Journal of Case Reports, 2025)
This case study explores the complex etiology of bilateral stroke in a 35-year-old female with Takayasu arteritis and antiphospholipid syndrome. The patient presented with altered sensorium and recurrent seizures, with imaging indicating large-vessel involvement. Management included anti-thrombotic and anti-platelet therapy, immunosuppressants, and antibiotics, targeting both vasculitis and thrombotic complications. The inflammatory state posed challenges in proceeding with interventions, highlighting the need for careful risk assessment. This case underscores the interplay of autoimmune disorders in stroke pathogenesis, emphasizing the necessity of a multidisciplinary approach to optimize patient care and improve long-term outcomes.